Analysis of the Readiness Level of Research Result of Gambier Sector Products Innovation in Andalas University - Fithri, Prima; Triawan, Fandy; Andiny, Rahima (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
One of the universities that is intensified to conduct research in producing innovative products is Andalas University (UNAND). Andalas University has 83 innovative products, including Gambier products from processing in the Teaching Industry Gambier UNAND. These processed Gambier products have not all been successfully commercialized. The obstacle usually experienced is that inventors need help knowing how to commercialize the product and whether the product has innovated. This study aims to determine the level of innovation readiness of three products in the Gambier sector that have never been studied before. Data collection was carried out through interviews with each product inventor and filling out questionnaires on the Katsinov Meter measuring instrument. Analysis of the measurement results was carried out using a fishbone diagram. Based on measurements, Fitopure (+)- Catechin and Unca Tea products are at Katsinov level 4 and level 2, respectively. Meanwhile, the scrub of Gambier products did not pass any Katsinov level. Some of the causes are that there is no business model concept, the Company has yet to conduct market research, it has not finished identifying market expansion needs, and it has not finished assessing technological and financial risks. Suggestions that can be given are that the Company needs to form a business model concept, conduct market research, expand the market, and assess technological and financial risks